High versus low positive end-expiratory pressure (PEEP) levels for mechanically ventilated adult patients with acute lung injury and acute respiratory distress syndrome - Cruz, Roberto Santa; Villarejo, Fernando; Irrazabal, Celica; Ciapponi, Agustin (My University, 2021)
Background In patients with acute lung injury (ALI) and acute respiratory distress syndrome (ARDS), mortality remains high. These patients require mechanical ventilation, which has been associated with ventilator-induced lung injury. High levels of positive end-expiratory pressure (PEEP) could reduce this condition and improve patient survival. This is an updated version of the review first published in 2013. Objectives To assess the benefits and harms of high versus low levels of PEEP in adults with ALI and ARDS. Search methods For our previous review, we searched databases from inception until 2013. For this updated review, we searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, LILACS, and the Web of Science from inception until May 2020.We also searched for ongoingtrials(www.thalscentral.org; www.clinicaltrial.gov; www.controlled-trials.com), and we screened the reference lists of included studies. Selection criteria We included randomised controlled trials that compared high versus low levels of PEEP in ALI and ARDS participants who were intubated and mechanically ventilated in intensive care for at least 24 hours. Data collection and analysis Two review authors assessed risk of bias and extracted data independently. We contacted investigators to identify additional published and unpublished studies. We used standard methodological procedures expected by Cochrane. Main results We included four new studies (1343 participants) in this review update. In total, we included 10 studies (3851 participants). We found evidence of risk of bias in six studies, and the remaining studies fulfilled all criteria for low risk of bias. In eight studies (3703 participants), a comparison was made between high and low levels of PEEP, with the same tidal volume in both groups. In the remaining two studies (148 participants), the tidal volume was different between high-and low-level groups. In the main analysis, we assessed mortality occurring before hospital discharge only in studies that compared high versus low PEEP, with the same tidal volume in both groups. Evidence suggests that high PEEP may result in little to no difference in mortality compared to low PEEP (risk ratio (RR) 0.97, 95% confidence interval (CI) 0.90 to 1.04; I-2 = 15%; 7 studies, 3640 participants; moderate-certainty evidence). In addition, high PEEP may result in little to no difference in barotrauma (RR 1.00, 95% CI 0.64 to 1.57; I-2 = 63%; 9 studies, 3791 participants; low-certainty evidence). High PEEP may improve oxygenation in patients up to the first and third days of mechanical ventilation (first day: mean difference (MD) 51.03, 95% CI 35.86 to 66.20;I-2 = 85%; 6 studies, 2594 participants; low-certainty evidence; third day: MD 50.32, 95% CI 34.92 to 65.72;I-2= 83%; 6 studies, 2309 participants; low-certainty evidence) and probably improves oxygenation up to the seventh day (MD 28.52, 95% CI 20.82 to 36.21; I-2 = 0%; 5 studies, 1611 participants; moderate-certainty evidence). Evidence suggests that high PEEP results in little to no difference in the number of ventilator-free days (MD 0.45, 95% CI-2.02 to 2.92;I-2= 81%; 3 studies, 1654 participants; low-certainty evidence). Available data were insufficient to pool the evidence for length of stay in the intensive care unit. Authors' conclusions Moderate-certainty evidence shows that high levels compared to low levels of PEEP do not reduce mortality before hospital discharge. Low-certainty evidence suggests that high levels of PEEP result in little to no difference in the risk of barotrauma. Low-certainty evidence also suggests that high levels of PEEP improve oxygenation up to the first and third days of mechanical ventilation, and moderate-certainty evidence indicates that high levels of PEEP improve oxygenation up to the seventh day of mechanical ventilation. As in our previous review, we found clinical heterogeneity-mainly within participant characteristics and methods of titrating PEEP-that does not allow us to draw definitive conclusions regarding the use of high levels of PEEP in patients with ALI and ARDS. Further studies should aim to determine the appropriate method of using high levels of PEEP and the advantages and disadvantages associated with high levels of PEEP in different ARDS and ALI patient populations.
Keywords: Positive End-Expiratory Pressure